Anti-corrosive and oil sensitive coatings based on epoxy/polyaniline/magnetite-clay composites through diazonium interfacial chemistry - Khouloud Jlassi (14152731) (2022)
Epoxy polymer nanocomposites filled with magnetite (Fe3O4) clay (B), named (B-DPA-PANI@Fe3O4) have been prepared at different filler loading (0.1, 0.5, 1, 3, 5 wt. %). The surface modification of clay by polyaniline (PANI) is achieved in the presence of 4-diphenylamine diazonium salt (DPA). The effects of the nanofiller loading on Tensile, mechanical and dielectric properties were systematically studied. Improved properties was highlighted for all reinforced samples. The addition of only 3 wt. % of the filler enhanced the tensile strength of the composites by 256%, and the glass transition temperature Tg by 37%. The dielectric spectra over a broad frequency showed a robust interface between the hybrid (B-DPA-PANI@Fe3O4) fillers and epoxy matrix. The results showed most significant improvement in corrosion inhibition using electrochemical impedance spectroscopy (EIS) in 3.5 wt % NaCl, as well as a significant response in oil sensing test. High charge transfer resistance of 110 × 106 Ω.cm2 using 3-wt % of filler was noted compared to 0.35 × 106 Ω.cm2 for the pure epoxy. The results obtained herein will open new routes for the preparation of efficient anticorrosion sensor coatings. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1038/s41598-018-31508-0